MODERASI BERAGAMA: URGENSI DAN KONDISI KEBERAGAMAAN DI INDONESIA - Afroh Nailil Hikmah; Ibnu Chudzaifah (Al-Fikr: Jurnal Pendidikan Islam, 2022)
Cultural diversity (multicultural) is a natural event due to the meeting of various cultures, the interaction of various individuals and groups carrying cultural behavior, having different and specific ways of life. Diversities such as cultural diversity, family background, religion, and ethnicity interact with each other in the Indonesian community. In horizontal communication between communities, Mulyana said, clashes between tribes are still taking place in various areas, ranging from stereotypes and prejudices between tribes, discrimination, to open conflicts and massacres between tribes that take lives. Competition between tribes is not only in the community but also among political elites and even academics to occupy positions in various agencies. This study aims to explain the importance of being moderate in religion and also to see how the conditions of religion in Indonesia are through descriptive qualitative research. The results of this study are 1) Moderation of religion as an effort to always maintain that whatever variety of interpretations and understandings of religion are maintained according to the corridor so as not to bring up extreme religious ways. Because the main points of religious teachings are basically the same, such as humanity, justice, equality before the law, respect for human rights and other universal values. 2) Based on research conducted by the Ministry of Religion, it shows that the 2021 Religious Harmony Index (KUB) is in the good category. Its value is at the national average of 72.39, up 4.93 points from the previous year.